Zakat Distribution for Handling Transgender in Indonesia: A Perspective of Maṣlāḥah Mursalaḥ - Usman, M (Islamic Family Law Department, Sharia and Law Faculty, Universitas Islam Negeri Ar-Raniry, 2023)
This study focuses urgent issue directly related to whether the LGBT community is eligible as a mustahik right holder (zakat recipient) under Islamic law. This study is a normative legal study using the maṣlāḥah mursalaḥ approach. The data analyzed is literature from books of fiqh scholars, textbooks, scientific journals, and other sources. Result of this study shows that Islam can regulate the management of zakat assets through the socio-economic empowerment of the people, preventing wealth accumulation in one group and reducing poverty. Mustahik, previously limited to short-term goals and institutional charity, now appears to have long-term benefits, including reducing poverty and empowering the community's economy. Mustahik is also useful for marginalized people, people with disabilities, and people experiencing moral and social deprivation, including mental health. The fact that the spread of this group is not limited to social media, but has also spread to campuses, schools, and being part of modern lifestyle needs urgent responses from various stakeholders, particularly in distributing zakat for LGBT community in Indonesia. The LGBT group is a legal reality that arises due to psychological and medical factors and entities caused by deviant associations. This research contributes to the Indonesian government's strategic steps to address the LGBT through zakat empowerment. So that in this way the group slowly through rehabilitation using zakat they experience awareness about life behavior that is in accordance with Islamic law in a dignified way.